2014
DOI: 10.1111/flan.12117
|View full text |Cite
|
Sign up to set email alerts
|

World Language Teacher Candidate Performance on edTPA: An Exploratory Study

Abstract: Federal and state legislation continues to promote teacher accountability in the United States. The new edTPA, a subject‐specific teacher performance assessment, is purported to measure beginning teacher readiness and is being pilot tested and implemented for licensure and certification decisions across the country. In this exploratory quantitative study, the researchers examined edTPA scores of 21 world language teacher candidates from two teacher preparation programs and compared those results to the cut sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 20 publications
(24 reference statements)
0
28
0
Order By: Relevance
“…In a study investigating the relationship between world language teacher candidate performance on various performance-based assessments, including edTPA, Russell and Davidson Devall (2016) found that candidates earned the lowest scores on task 3 (assessment), with an average rubric score of 2.46 of a possible score of 5. In their study involving world language teacher candidates, Hildebrandt and Swanson (2014) also found that candidates earned the lowest scores on task 3. According to the results, many of the candidates had difficulty providing suggestions to improve student performance (rubric 12) and using assessment results to inform instruction (rubric 13).…”
Section: Teacher Candidate Performancementioning
confidence: 96%
See 1 more Smart Citation
“…In a study investigating the relationship between world language teacher candidate performance on various performance-based assessments, including edTPA, Russell and Davidson Devall (2016) found that candidates earned the lowest scores on task 3 (assessment), with an average rubric score of 2.46 of a possible score of 5. In their study involving world language teacher candidates, Hildebrandt and Swanson (2014) also found that candidates earned the lowest scores on task 3. According to the results, many of the candidates had difficulty providing suggestions to improve student performance (rubric 12) and using assessment results to inform instruction (rubric 13).…”
Section: Teacher Candidate Performancementioning
confidence: 96%
“…An overview of research focusing on edTPA has shown an evolution since the assessment's introduction to the teaching profession. Initial studies focused on candidate results in early‐adopting programs and highlighted areas where many candidates needed improvement (Burns, Henry, & Lindauer, ; Denton, ; Hildebrandt & Swanson, ). Researchers then began investigating the performance of specific groups of teacher candidates, specifically non‐native speakers of English (Kissau & Algozzine, ; Russell & Davidson Devall, ; Troyan & Kaplan, ), suggesting possible bias in the assessment.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…WL teacher sustainability needs active efforts building on current research and comprehensive data, with clear implementation goals and dedicated funding and leadership in order to arrest the decline of teachers. Such efforts include: seeking ways to decrease the cost of becoming a teacher; e.g., the cost is more than $800 in Georgia (Hildebrandt & Swanson, ), of which most is for testing—which does not correlate to teacher effectiveness. funding longitudinal studies and programs that aim to add to the research base and build the supply of WL teachers; looking to other countries and jurisdictions for models of success; making explicit demands of schools in terms of how they implement, fund, and manage WL programs; providing bonuses or subsidies to teachers with the relevant skills and knowledge to move into WL teaching positions; and providing WL teachers with the time to engage in professional development and networking. …”
Section: An Immediate Change Of Strategymentioning
confidence: 99%
“…The sudden appearance and broad implementation of edTPA on the national stage has stimulated discussion as well as research on the topic of novice teacher preparation and program accountability in the United States. Consistent with a growing body of research that has revealed issues with the WL edTPA in particular (e.g., Behney, ; Hildebrandt & Swanson, ; Jourdain, ; Kissau & Algozzine, ; Russell & Davidson Devall, ; Troyan & Kaplan, ), one hopes that SCALE will embrace partnerships with content experts and move toward a more collaborative model for holding teacher preparation institutions to high but attainable standards and expectations. As stated by Cochran‐Smith et al, “joint decision making among relevant stakeholders” (2018, p. 170) is needed to negotiate the very problematic issues of power—control, content, and consequences—to co‐create a national assessment that reflects the knowledge and skills that can reasonably be attained by beginning WL teachers over the course of a four‐ or five‐year undergraduate or master of arts in teaching program of study and that will position them to be successful working with diverse learners across diverse instructional levels and contexts.…”
Section: Resultsmentioning
confidence: 86%
“…A number of studies have highlighted the assessment's potential to effectively assess aspiring teachers’ knowledge and skills across varying subjects (Youngs & Whittaker, ), but edTPA has motivated only a modest amount of content‐specific research interest, with the exception of, for example, An () in elementary education; Castellano, Duckor, and Wihardini () in elementary mathematics; and Heil and Berg () in music education. In contrast, the impact of the WL edTPA on WL teacher education programs seems to have provided a rich area of investigation (e.g., Behney, ; Hildebrandt & Swanson, ; Jourdain, ; Kissau & Algozzine, ; Okraski & Kissau, ; Russell & Davidson Devall, ; Swanson & Hildebrandt, ; Troyan & Kaplan, ). The present study sought to supplement that existing literature by investigating WL teacher educators’ perceptions of edTPA and its impact on WL teacher education programs.…”
Section: Introductionmentioning
confidence: 99%